2014
DOI: 10.1261/rna.041657.113
|View full text |Cite
|
Sign up to set email alerts
|

Fast-evolving microRNAs are highly expressed in the early embryo of Drosophila virilis

Abstract: MicroRNAs are short non-protein-coding RNAs that regulate gene expression at the post-transcriptional level and are essential for the embryonic development of multicellular animals. Comparative genome-scale analyses have revealed that metazoan evolution is accompanied by the continuous acquisition of novel microRNA genes. This suggests that novel microRNAs may promote innovation and diversity in development. We determined the evolutionary origins of extant Drosophila microRNAs and estimated the sequence diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
61
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(72 citation statements)
references
References 76 publications
9
61
2
Order By: Relevance
“…The evolution of the pan-Drosophilid mir-309/3/286/4/5/6-1,2,3 (i.e., mir-306 6) cluster was recently examined by Griffiths-Jones and colleagues, and our analysis agrees with theirs for the species analyzed (Ninova et al 2014). We extended this analysis by identifying proto-mir-309 clusters in two ant species, for which none of the resident miRNAs had been previously annotated (Fig.…”
Section: Acquisition Of Multiple Seed Family Classes In the Eight Memsupporting
confidence: 88%
“…The evolution of the pan-Drosophilid mir-309/3/286/4/5/6-1,2,3 (i.e., mir-306 6) cluster was recently examined by Griffiths-Jones and colleagues, and our analysis agrees with theirs for the species analyzed (Ninova et al 2014). We extended this analysis by identifying proto-mir-309 clusters in two ant species, for which none of the resident miRNAs had been previously annotated (Fig.…”
Section: Acquisition Of Multiple Seed Family Classes In the Eight Memsupporting
confidence: 88%
“…It has been shown in Drosophila that the miR-309 cluster could promote mRNA turnover during the maternal-to-zygotic transition and, thus, lead to reduced survival and delayed larval development (18). Here, our results have demonstrated that miR-309 acts to initiate ovarian development appropriately in the mosquito A. aegypti.…”
Section: Discussionsupporting
confidence: 61%
“…Recently, a fast-evolving miRNA cluster mir-309∼6 has been identified, which is undergoing particularly dynamic evolutionary events within the arthropod lineage, including duplication, gain, and/or loss of miRNA members within it (18). In Drosophila, this miRNA cluster is preferentially expressed in eggs and promotes mRNA turnover during the maternal-to-zygotic transition (19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the most abundant microRNAs in the beetle oocyte belong to two clusters: mir-279e 2944c and mir-3889 3843. These are diverged homologs of the Drosophila mir-309 6 and mir-994 318 (Ninova et al 2014), whose maternal deposition in Drosophila is modest. The maternal microRNA complement of T. castaneum also contains a number of lineage-specific microRNAs, including the members of the massively duplicated 40 miRNA gene cluster on the X Chromosome, albeit at lower concentrations (Supplemental Table 2).…”
Section: Resultsmentioning
confidence: 99%